Critical Thinking Activities to Improve Senior High School Students’ Speaking Skills - Yuniar Chrismonia Caesar (AL-ISHLAH: Jurnal Pendidikan, 2023)
Many professionals emphasize the importance of teaching English with critical thinking skills, but implementation is still scant, especially in Indonesia ELT. This research investigates the use of critical thinking activities to teach EFL learners speaking skills, describes the challenges teachers and students face, and explains how they overcome them. Foreign Language Department Institute (FLDI) of the Boarding School at Probolinggo completed the research. This descriptive qualitative study used observation, interviews, and documentation for data. Three steps—reducing, showing, and concluding—analyzed the data. This study indicated that FLDI implemented critical thinking through speech, debate, and discussion. Those exercises engaged students throughout the process, allowing them to speak up and think critically. The research also revealed teacher concerns regarding student critical thinking, speaking, and boredom. Students also struggled in critical reading, speaking, and article writing. This study showed how teachers and students used icebreakers, reading and writing instruction, vocabulary memorization, and intensive engagement to overcome such challenges. This study encourages EFL teachers to provide comprehensive tasks to help students practice speaking and thinking. This study may also help EFL teachers and students with speaking issues.